Analisis Kedaulatan Allah Yang Mengalir Bagi Umat-Nya Melalui Pribadi Ezra Dalam Konteks Ezra 1:1-6 - Andreas Yonatan Gultom; Timotius Toni Simanjuntak; Herdiana Sihombing (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
This article deeply explores the concept of God's sovereignty flowing to His people through the person of Ezra, focusing on the text of Ezra 1:1-6. This research aims to gain a fuller understanding of how God expresses His sovereignty through Ezra's role in guiding His people. The research methods used include analysis of the biblical text, study of historical studies, and exposure to the cultural context of the time. The findings provide a rich and complex view of Ezra's role as a channel of God's will in restoring and guiding His people.